P4HA1: A single-gene surrogate of hypoxia signatures in oral squamous cell carcinoma patients. (August 2017) - Kappler, Matthias; Kotrba, Johanna; Kaune, Tom; Bache, Matthias; Rot, Swetlana; Bethmann, Daniel; Wichmann, Henri; Güttler, Antje; Bilkenroth, Udo; Horter, Susanne; Gallwitz, Lisa; Kessler, Jacqueline; et al.
Abstract: Background and purpose: Hypoxia gene expression signatures are of high prognostic value for head and neck cancer patients. Recently, the prognostic information of a multiple-gene hypoxia signature was found to be provided by the mRNA level of P4HA1 alone (Tawk et al., 2016). Therefore, we studied the prognostic value of P4HA1 in an independent cohort of oral squamous cell carcinoma (OSCC) patients. Material and methods: Frozen tumor samples of 118 adult OSCC patients were analysed for P4HA1 mRNA level by quantitative real-time TaqMan™ PCR analysis. Kaplan-Meier analysis and Cox's regression analysis were performed to characterize the prognostic impact of P4HA1 mRNA level in OSCC patients. Results: The analyzed patient cohort was divided into four subgroups according to the quartiles of the P4HA1 mRNA levels. The highest intratumoral P4HA1 mRNA level was significantly correlated with a poor overall survival (RR = 2.2; P = 0.04) and an increased risk of locoregional recurrence (RR = 4.8; P = 0.02). In patients who received radiotherapy ( n = 82) highest intratumoral P4HA1 mRNA level was significantly correlated with a poor overall survival (RR = 3.4; P = 0.01) and an increased risk of locoregional recurrence (RR = 10.3; P = 0.005). Moreover, significant correlations between the P4HA1 mRNA level and the mRNA level of several EMT and stem cell markers were found. Conclusions: A high P4HA1 mRNA level, as a single-gene surrogate of hypoxia, is an independent prognostic marker for the overall survival and locoregional recurrence of OSCC patients.